Psychological burnout and its relationship to the quality of life of mothers of children with autism in the centers for people with special needs in Khartoum - Alkashef, Sarah Mohamed Ahmed (Journal of Educational and Psychological Sciences, 2023)
The research aims to find out the level of psychological burnout among mothers of autistic children and its relationship with the quality of life at special needs centers in Khartoum. The researcher followed the relational descriptive approach as the most appropriate approach for such research, as the sample consisted of (108) mothers of autistic children, and to collect data, the researcher used the psychological burnout scale from her numbers and the quality of life scale from her numbers to analyze the research data, the researcher followed the statistical package program for Social Sciences (SPSS) and also، The Pearson correlation coefficient and the mono-contrast test of two samples had the results: there were no differences in age-enhanced psychomotor fatigue. There are also no differences in age depending on the sub-dimensions of the psychological burnout scale (psychological stress and dissatisfaction), and there are differences in psychological burnout depending on the dimension of the negative trend and the presence of differences in the age stages between (24-35). One of the recommendations is the work of counseling programs implemented by psychologists to enhance psychological compatibility and raise awareness of the level of quality of life.